Peningkatan Pengetahuan Pemasaran Melalui Media Sosial Bagi Petani Desa Sukaraja Baru Indralaya Selatan - Lishapsari Prihatini; Icuk M. Sakir; Wahidin Wahidin; Agustin Rozalena; Dody Saputra Jaya; Windi Rafila Putri (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2023)
The problem experienced by Sukaraja Baru Village, South Indralaya District, Ogan Ilir Regency is the limitations in marketing the production of fruit seeds that are produced from generation to generation. In fact, the production of fruit seed cultivation carried out by farmers in Sukaraja Baru Village is very varied. Several types of fruit seeds are cultivated, such as key citrus fruits, longan, water guava, durian, and others. However, it is miserable that this very large asset is still not being noticed or not known by the general public, especially South Sumatra. This is due to the lack of promotion or dissemination of information on this fruit seed center. Therefore, the pur this activity aims to increase farmers' knowledge keting their fruit nurseries. The implementation method for this assistance is through counseling and training aimed at increasing the knowledgeimprovingties of farmers. The results of this training activity show that farmers' knowledge of understanding the benefits of social media as an alternative to promoting fruit seed production. In addition, farmers also get experience creating content for social media, such as Instagram and Facebook.